RETRACTED: Immediacy as a better service: Analysis of limitations of the use of ChatGPT in library services - Yamson, George Clifford (Information development, 2025)
The paper examines ChatGPT's application in library services and assesses its shortcomings. The study emphasizes the immediateness that new technologies offer to library services and how ChatGPT falls short of satisfying this demand because it relies on pre-existing data and lacks real-time interaction. The paper suggests that while ChatGPT can assist in basic inquiries, it cannot replace human interaction and expertise in addressing more complex questions and concerns. The study suggests that libraries should give preference to efficient and individualized service to better meet the demands of their patrons. The study provides valuable insights for libraries and other service organizations considering the implementation of chatbots or similar AI technologies.